1985
DOI: 10.1042/bj2290127
|View full text |Cite
|
Sign up to set email alerts
|

Differences between collagen hydroxylases and 2-oxoglutarate dehydrogenase in their inhibition by structural analogues of 2-oxoglutarate

Abstract: Inhibition of lysyl hydroxylase and prolyl 3-hydroxylase was studied with 23 selected aromatic and aliphatic structural analogues of 2-oxoglutarate and the results were compared with those previously reported for prolyl 4-hydroxylase. All the compounds inhibited the hydroxylases competitively with respect to 2-oxoglutarate and noncompetitively with respect to Fe2+ and the peptide substrate. The inhibition patterns for the three collagen hydroxylases were basically similar, but certain differences in detail eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 18 publications
3
40
0
Order By: Relevance
“…The fact that the effect of coumalic acid is more marked with chick-embryo prolyl 4-hydroxylase than with lysyl hydroxylase or human prolyl 4-hydroxylase is not surprising, because the structure-activity relationships from which the structure of coumalic acid was deduced as a potential inactivator (Majamaa et al, , 1986 were established with chick enzyme, and lysyl hydroxylase has been reported to show a lower affinity towards both 2-oxoglutarate and its competitive antagonists (Majamaa et al, 1985). Our data also indicate that the Km of 2-oxoglutarate for human prolyl 4-hydroxylase is 40 /M, compared with 22 fM for the chick enzyme, and accordingly the Ki values of the competitive 2-oxoglutarate analogues were approximately twice those reported for the chick enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the effect of coumalic acid is more marked with chick-embryo prolyl 4-hydroxylase than with lysyl hydroxylase or human prolyl 4-hydroxylase is not surprising, because the structure-activity relationships from which the structure of coumalic acid was deduced as a potential inactivator (Majamaa et al, , 1986 were established with chick enzyme, and lysyl hydroxylase has been reported to show a lower affinity towards both 2-oxoglutarate and its competitive antagonists (Majamaa et al, 1985). Our data also indicate that the Km of 2-oxoglutarate for human prolyl 4-hydroxylase is 40 /M, compared with 22 fM for the chick enzyme, and accordingly the Ki values of the competitive 2-oxoglutarate analogues were approximately twice those reported for the chick enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the putative subsite 111 of the 2-oxoglutarate-binding site, which probably interacts with the aliphatic C3-C4 region of the cosubstrate was assumed to have the weakest influence on the binding, earlier studies on the enzymes of this class [3, 1 1 , 12, 401 demonstrated that a hydrophobic area between the other two domains of 2-oxoglutarate was important for an effec-tive interaction with the cosubstrate or with its structural analogues, as could be shown by loss of [3,11,121 or reduction of [40] catalytic activity when oxalacetate or acetone dicarboxylate was tested for their ability to replace the cosubstrate in the enzyme reaction. Furthermore, it is remarkable that the addition of an extra methylene group between the a-ketoacid group and the free carboxyl group, as in 2-oxoadipate, led to an effective cosubstrate for 2,4-dichlorophenoxyacetate/2-oxoglutarate dioxygenase [40], for prolyl4-hydroxylase [ll], and for lysyl hydroxylase [12]. Moreover, in the present work significant catalytic activity of FHT was observed when 2-oxoadipate was tested for the ability to replace 2-oxoglutarate.…”
Section: Discussionmentioning
confidence: 99%
“…The two potential interactions of PQQ with iron atoms are indicated by the encircled 'A' and 'B'. 'A' designates the bidentate mode of coordination to the catalytic site Fe 2+ of prolyl 4-hydroxylase that is indispensible for effective and specific inhibition; 'B' designates the terdentate mode of coordination that is not possible at this enzyme's co-substrate-binding site and that can occur only in solution, resulting in nonspecific inhibition [17][18][19]43]. PQQ displays II, llI and IV as substructures.…”
Section: Hypothesismentioning
confidence: 99%
“…Designed and predicted to interfere with the decarboxylation phase of the catalytic cycle of prolyl 4-hydroxylase as formulated by Hanauske-Abel and Gtinzler, HAG [16,32], compounds like 3,4-dihydroxyphenylacetate (3,4-DHPA) and pyridine-2,4-dicarboxylate (2,4-PDCA), representative structures for class IV and class V inhibitors of the HAG mechanism [16], were immediately found to be the enzyme's most potent reversible inhibitors presently available [17][18][19] [19], the two cosubstrates of prolyl 4-hydroxylase [12,20]. 2,4-PDCA was demonstrated to select for the 2-oxoglutarate-binding site of only the collagen hydroxylases [18] and to inhibit specifically the biosynthesis of hydroxyproline-dependent proteins, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation